Produção localizada e inovação: o arranjo produtivo local de fruticultura irrigada na microrregião do Baixo Jaguaribe, no estado do Ceará - Campos, Kilmer Coelho (2008)
Brazil is the world's third pole of fruit, with an annual output of about 38 million tons. In the Northeast, agribusiness fruit is of fundamental importance for the country, because the total value of exports Northeastern corresponds to 57% of Brazilian exports of fruit. Ceará stands out in the regional and national levels, through 12 agricultural goods in 2003 accounted for about 50% of total exports from Ceará, especially cashew-nut of, hides and skins, shrimp, lobster and fruit . In the Northeast, specifically in Ceará, agricultural activities are developed primarily by low-income farmers, because the region concentrates the May number of family farms in Brazil. In this context, the marketing of Brazilian fruits in the domestic and international strategy is to give jobs, income and foreign exchange for the country Earn highlight the processes of development and analysis of local competitive advantages, by the insertion of local clusters (APL) innovative since, in recent years, industrial policies and development began to pay particular attention to the training of these arrangements and production systems. In this perspective, framed to analyze the proposed local productive arrangement of irrigated fruit located in the municipalities of Limon and Russian North in the state of Ceará. It was intended to characterize the productive structure of the arrangement, identifying potential sites and the performance of institutional configurations and agents, production and innovation, providing its best development in APL. The identification and characterization of the structure of APL fruit were based on the neo-Schumpeterian approach on local innovation systems. Factor analysis and cluster allowed the reduction of the data and the identification of distinct groups of producers, in order to support the calculation of an index hierarchy representing the degree of innovation, identifying a core or group of producers responsible for developing the APL or that encourages interaction activities, cooperation and learning within the arrangement, stimulating productive activities and innovative sites. Found the existence of APL formed by micro, small, medium and large producers located in the same region, where there is great diversity of actions and stakeholders around the activity, developing innovative processes and collective learning, transmitted by tacit knowledge and experiences cooperation shared between producers and institutions, promoting the growth and development of the micro-irrigated horticulture. Using the technique of factor analysis to summarize the information contained in the 17 explanatory variables used in the study, four factors, innovative and productive level (F1), level of training and information (F2), technological level and cooperative (F3) and level intellectual (F4) of the producers of APL. The development of irrigated horticulture APL micro Lower Jaguaribe in Ceará is supported by a group of producers more integrated and intensive production processes, innovation, cooperation and interactive learning, and relationships developed at the local level. The existence of this APL entails positive returns for producers and an important instrument for generating employment and income, and regional development. Geographical proximity and innovation cooperation activities and strengthen the dissemination of knowledge production and marketing of fruits in the region. Among the effective public policies that could contribute to the further growth and development of the activity, we suggest the supply of electricity-related subsidies, improvements in transport infrastructure, and dissemination of actions accompanied by an efficient marketing service product of APL.